Single‐ Versus 2‐Stent Strategies for Coronary Bifurcation Lesions: A Systematic Review and Meta‐Analysis of Randomized Trials With Long‐Term Follow‐up. Issue 11 (23 September 0207) - Ford, Thomas J.; McCartney, Peter; Corcoran, David; Collison, Damien; Hennigan, Barry; McEntegart, Margaret; Hildick‐Smith, David; Oldroyd, Keith G.; Berry, Colin
Abstract : Background: The majority of coronary bifurcation lesions are treated with a provisional single‐stent strategy rather than an up‐front 2‐stent strategy. This approach is supported by multiple randomized controlled clinical trials with short‐ to medium‐term follow‐up; however, long‐term follow‐up data is evolving from many data sets. Methods and Results: Meta‐analysis of randomized controlled trials evaluating long‐term outcomes (≥1 year) according to treatment strategy for coronary bifurcation lesions. Nine randomized controlled trials with 3265 patients reported long‐term clinical outcomes at mean weighted follow‐up of 3.1±1.8 years. Provisional single stenting was associated with lower all‐cause mortality (2.94% versus 4.23%; risk ratio: 0.69; 95% confidence interval, 0.48–1.00; P =0.049; I 2 =0). There was no difference in major adverse cardiac events (15.8% versus 15.4%; P =0.79), myocardial infarction (4.8% versus 5.5%; P =0.51), target lesion revascularization (9.3% versus 7.6%; P =0.19), or stent thrombosis (1.8% versus 1.6%; P =0.28) between the groups. Prespecified sensitivity analysis of long‐term mortality at a mean of 4.7 years of follow‐up showed that the provisional single‐stent strategy was associated with reduced all‐cause mortality (3.9% versus 6.2%; risk ratio: 0.63; 95% confidence interval, 0.42–0.97; P =0.036; I 2 =0). Conclusions: Coronary bifurcation percutaneous coronary intervention using a provisional single‐stent strategy is associated with a reduction in all‐cause mortality at long‐term follow‐up.